Wear-resistant nylon sleeve and preparation method thereof

By using modified self-lubricating microcapsules and ionic liquids in nylon sleeves, the problem of microcapsules breakage during nylon sleeve manufacturing is solved, and the good self-lubricating and wear resistance of nylon sleeves is achieved, ensuring the wear resistance effect for long-term use .

CN119144148APending Publication Date: 2024-12-17HEBEI XINKEMING RUBBER & PLASTIC PRODUCTS CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411405652.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The existing nylon sleeves are prone to breakage during the manufacturing process, resulting in insufficient wear resistance and unable to meet market demand.

Method used

By centrifugal reaction and modification of microcapsule material, the binding force of microcapsules is enhanced by adding modified self-lubricating microcapsules to the nylon sleeve, and the epoxy group reacts with nylon 6-terminal active groups, and the binding force of microcapsules is enhanced and wrapped on the surface. The precursor layer is used to increase structural strength and avoid damage, while forming a friction chemical reaction film with ionic liquid to reduce wear and resist wear.

Benefits of technology

The good self-lubricating properties and wear resistance of the nylon sleeve are achieved, which avoids premature damage to the microcapsules, ensures wear resistance for long-term use, and improves friction performance by friction chemical reaction film and precursor layer.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of high polymer materials, in particular to a wear-resistant nylon sleeve and a preparation method thereof.The wear-resistant nylon sleeve is prepared from, by weight, 90-100 parts of nylon 6, 6-8 parts of self-lubricating microcapsules, 1-1.2 parts of carbon black, 2-3 parts of flame retardant and 0.8-1 part of antioxidant; according to the self-lubricating nylon sleeve, the self-lubricating microcapsules are added into the nylon sleeve, and the self-lubricating microcapsules are prevented from being damaged in the preparation process of the nylon sleeve through centrifugal reaction and modification of the microcapsule wall material, and meanwhile, the nylon sleeve has a good self-lubricating property and keeps good wear resistance in the long-term use process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a wear-resistant nylon sleeve and a preparation method thereof. Background Art

[0002] In mining machinery, nylon sleeves are a common component for the operation of mechanical equipment. Nylon sleeves are widely used in the protection, support and positioning of mechanical parts such as bearings, gears, and transmission devices.

[0003] Currently, the commonly used nylon sleeves mostly use nylon 6 as the main material, which has the advantages of high strength, high toughness, high modulus, high chemical stability, easy processing and molding, and low cost. However, the existing nylon 6 material still has the problems of large friction coefficient and wear. During long-term use, the nylon sleeve will inevitably wear out, resulting in a low service life of the nylon sleeve. In order to improve the wear resistance of the nylon sleeve, self-lubricating microcapsules are usually added during the production process of the nylon sleeve to make the nylon sleeve have self-lubricating properties. However, most of the current microcapsule structures cannot withstand the mechanical pressure during the manufacturing process of the nylon sleeve, resulting in premature damage to the microcapsules, affecting the use of the nylon sleeve and failing to meet market demand. Summary of the invention

[0004] The purpose of the present invention is to provide a wear-resistant nylon sleeve and a preparation method thereof. Through centrifugal reaction and modification of the microcapsule wall material, the problem of self-lubricating microcapsule breakage in the existing nylon sleeve preparation process is solved. At the same time, the nylon sleeve has good self-lubricating properties and maintains good wear resistance during long-term use.

[0005] The object of the present invention can be achieved by the following technical scheme: A method for preparing a wear-resistant nylon sleeve, comprising the following steps: Step S1: weighing the following raw materials in parts by weight: 90-100 parts of nylon 6, 6-8 parts of self-lubricating microcapsules, 1-1.2 parts of carbon black, 2-3 parts of flame retardant and 0.8-1 part of antioxidant; Step S2: mixing nylon 6, self-lubricating microcapsules, carbon black, flame retardant and antioxidant, removing water under vacuum and feeding into a mold, centrifuging and reacting for 20 minutes at a temperature of 180° C., demoulding and cooling to obtain a wear-resistant nylon sleeve; The self-lubricating microcapsules are prepared by the following steps: Step A1: polyvinyl alcohol and deionized water were mixed, stirred at a stirring rate of 300 rpm and a temperature of 85° C. for 1 hour, and then ammonia water was added to adjust the pH value to 8, and lignin and ionic liquid were added, and then hydrochloric acid solution was added to adjust the pH value to 3, and emulsified at a stirring rate of 8000 rpm for 10 minutes to obtain a composite emulsion; The mass concentration of ammonia water is 25%, the molar concentration of hydrochloric acid solution is 1 mol / L, and the dosage ratio of polyvinyl alcohol, deionized water, lignin and ionic liquid is 0.4-0.5g:120-150mL:0.8-1g:1.2-1.5g; During the reaction, lignin and ionic liquid are added to a polyvinyl alcohol solution and then emulsified. During the emulsification process, lignin nanoparticles are evenly dispersed around the droplets of the ionic liquid, thereby forming a uniform barrier film at the oil-water interface of the ionic liquid, thereby preparing a composite emulsion. Step A2: isophorone diisocyanate and triethylenetetramine are mixed, stirred at a stirring rate of 450-500 rpm and a temperature of 50°C, and then dripped into the composite emulsion for reaction for 3-4 hours to obtain single-wall microcapsules; tris(hydroxymethyl)aminomethane hydrochloride) solution and dopamine hydrochloride are mixed, stirred at a stirring rate of 120-150 rpm and a temperature of 40°C, and then added into the single-wall microcapsules for reaction for 0.5 hours; polyethyleneimine is then added, and the reaction is continued for 3-4 hours to obtain modified microcapsules; The dosage ratio of isophorone diisocyanate, triethylenetetramine and composite emulsion is 0.0014-0.0015 mol: 0.0012-0.0013 mol: 120-150 mL, the mass concentration of tris(hydroxymethyl)aminomethane hydrochloride solution is 1.2 g / L, the pH value is 8, the dosage ratio of tris(hydroxymethyl)aminomethane hydrochloride solution, dopamine hydrochloride, single-wall microcapsule and polyethyleneimine is 100-120 mL: 0.24-0.28 g: 0.04-0.05 g: 0.2 g; During the reaction, the isocyanate groups in isophorone diisocyanate react with the amino groups in triethylenetetramine, thereby forming a polyurethane layer on the barrier membrane of the ionic liquid in the composite emulsion to prepare single-wall microcapsules. Then, under alkaline conditions, dopamine in dopamine hydrochloride is wrapped on the surface of the single-wall microcapsules to form a polydopamine layer, and the surface is positively charged by introducing polyethyleneimine to prepare modified microcapsules. Step A3: Graphene oxide, ammonium tetrathiomolybdate and anhydrous ethanol are mixed, stirred at a stirring rate of 300 rpm and a temperature of 110°C, ascorbic acid is added, and the reaction is carried out for 3-4 hours to obtain a precursor, the precursor is mixed with deionized water, and ultrasonically dispersed for 10 minutes, stirred at a stirring rate of 150-180 rpm and room temperature, and modified microcapsules are added, and the reaction is carried out for 6-8 hours, and then 3-glycidyloxypropyltrimethoxysilane and anhydrous ethanol are added, and the reaction is carried out for 2-3 hours to obtain self-lubricating microcapsules; The amount ratio of graphene oxide, ammonium tetrathiomolybdate, anhydrous ethanol and ascorbic acid is 0.5-0.8 g: 1-1.2 g: 60-80 mL: 2-2.2 g, and the amount ratio of precursor, deionized water, modified microcapsule, 3-glycidyloxypropyltrimethoxysilane and anhydrous ethanol is 0.3-0.4 g: 100-120 mL: 1.5-2 g: 4.5-5 mL: 60-80 mL; During the reaction, ammonium tetrathiomolybdate is reduced to molybdenum disulfide by thermal decomposition with ascorbic acid as a reducing agent. Due to the negative charge of graphene oxide itself, the reduced molybdenum disulfide is evenly distributed on the graphene oxide sheet to obtain a precursor. Due to the negative charge of the precursor, it can be combined with the modified microcapsule with a positive charge to form a precursor layer. Then, 3-glycidyloxypropyltrimethoxysilane is added to perform epoxy modification on the microcapsule, and epoxy groups are introduced to obtain self-lubricating microcapsules. The ionic liquid is prepared by the following steps: Step B1: dimethyl chlorophosphate, hydroxyethyl acrylate and dichloromethane are mixed, stirred at a stirring rate of 120-150 rpm, at room temperature, triethylamine is added, and the reaction is carried out for 6-8 hours to obtain intermediate a; intermediate a, 3-amino-1-propanol and dimethyl sulfoxide are mixed, and the reaction is carried out for 24 hours under nitrogen protection, at a stirring rate of 120-150 rpm, and at a temperature of 60° C. to obtain intermediate b; intermediate b, 4-dimethylaminopyridine, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and dimethyl sulfoxide are mixed, and the reaction is carried out at a stirring rate of 120-150 rpm, at room temperature, thioctic acid is added, and the reaction is carried out for 24 hours to obtain intermediate c; The amount ratio of dimethyl chlorophosphate, hydroxyethyl acrylate and triethylamine is 0.1-0.12mol:0.12-0.14mol:12-13g, the amount ratio of intermediate a and 3-amino-1-propanol is 0.1-0.12mol:0.05mol, and the amount ratio of intermediate b, 4-dimethylaminopyridine, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and thioctic acid is 0.045-0.05mol:11-12g:18-19g:0.05-0.053mol; During the reaction, under the action of triethylamine, the chlorine in dimethyl chlorophosphate and the hydroxyl group in hydroxyethyl acrylate undergo a substitution reaction to introduce a double bond to obtain an intermediate a, the double bond in the intermediate a undergoes Michael addition with the amino group in 3-amino-1-propanol to form a tertiary amine group to obtain an intermediate b, and then under the action of 4-dimethylaminopyridine and 1-ethyl-(3-dimethylaminopropyl)carbodiimide, the hydroxyl group in the intermediate b undergoes an esterification reaction with the carboxyl group in lipoic acid to obtain an intermediate c; Step B2: 1-(3-aminopropyl)imidazole, 1,6-hexamethylene diisocyanate and chloroform were mixed, and the mixture was reacted for 4-6 hours at a stirring rate of 80-100 rpm and a temperature of 80°C to obtain intermediate d. Intermediate c, intermediate d and ether were mixed, and dicyclohexylcarbodiimide was added under stirring at a stirring rate of 80-100 rpm and a temperature of 40°C, and the mixture was reacted for 12-14 hours to obtain an ionic liquid. The ratio of 1-(3-aminopropyl)imidazole to 1,6-diisocyanatohexane is 0.1-0.11 mol: 0.05 mol, and the ratio of intermediate c, intermediate d and dicyclohexylcarbodiimide is 0.04-0.045 mol: 0.04-0.045 mol: 2.5-3 g; During the reaction, the amino group in 1-(3-aminopropyl)imidazole reacts with the isocyanate groups at both ends of 1,6-hexamethylene diisocyanate to form urea groups to obtain intermediate d. Then, under the action of dicyclohexylcarbodiimide, the methyl phosphate group in intermediate c reacts with the imidazole group in intermediate d, and the methyl group in the methyl phosphate group is transferred to the imidazole group, thereby forming a positively charged quaternary ammonium structure in the imidazole group, and the phosphate group that loses the methyl group is negatively charged, and then an ionic bond is formed between the two to obtain an ionic liquid. The beneficial effects of the invention are as follows: the invention discloses a wear-resistant nylon sleeve and a preparation method thereof. By adding self-lubricating microcapsules into the nylon sleeve, centrifugal reaction and modification of the wall material of the microcapsules, the damage of the self-lubricating microcapsules in the preparation process of the nylon sleeve is avoided, and the nylon sleeve has good self-lubricating properties and maintains good wear resistance during long-term use. In the preparation process of the nylon sleeve, the self-lubricating microcapsules are migrated to the outer surface of the nylon sleeve by centrifugation. At the same time, since epoxy groups are grafted on the surface of the self-lubricating microcapsules, the epoxy groups can react with the terminal active groups of nylon 6, so that the self-lubricating microcapsules can be better combined with the nylon 6 substrate, so that the external force is better transmitted to the microcapsules, and the uneven surface of the nylon sleeve is avoided. Since the surface of the microcapsules is wrapped with a precursor layer, the precursor layer can greatly improve the structural strength of the microcapsules, avoiding the premature damage of the microcapsules in the preparation process of the nylon sleeve. At the same time, when the nylon sleeve encounters external friction, the self-lubricating microcapsules on the surface are damaged by the external force, and the internal The ionic liquid core material flows out, and the ionic liquid wraps the damaged wall material to form a self-lubricating layer on the contact surface. Since the ionic liquid is prepared by the reaction of intermediate c and intermediate d, and intermediate c is a urea imidazole containing a twin structure, and intermediate d is a phosphate group containing a twin structure, both the urea imidazole and the phosphate group can react well with the metal to form a friction chemical reaction film during the friction process, which plays a role in reducing wear and resisting wear. At the same time, since the damaged wall material contains a large amount of precursors, and the precursor is a structure of sheet graphene oxide adsorbing nano-molybdenum disulfide, it can also exert certain anti-wear properties. At the same time, since intermediate d also contains thioctic acid groups, the thioctic acid groups will combine with defects in molybdenum disulfide in the precursor, as well as hydrogen bonds between the ionic liquid and the precursor, so that the ionic liquid and the precursor are non-covalently bonded, so that they not only cooperate with each other to exert better lubrication properties, but also avoid the wear of the substrate caused by the disordered accumulation of the precursor sheet structure, so that the nylon sleeve has good long-term self-lubricating and wear-resistant properties. DETAILED DESCRIPTION

[0006] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0007] Example 1 A method for preparing a wear-resistant nylon sleeve comprises the following steps: Step S1: weigh the following raw materials in parts by weight: 90 parts of commercially available Shunjie 200 mesh nylon 6, 6 parts of self-lubricating microcapsules, 1 part of carbon black, 2 parts of commercially available OP1240 flame retardant and 0.8 parts of commercially available 1010 antioxidant; Step S2: mixing nylon 6, self-lubricating microcapsules, carbon black, flame retardant and antioxidant, removing water under vacuum and feeding into a mold, centrifuging and reacting for 20 minutes at a temperature of 180° C., demoulding and cooling to obtain a wear-resistant nylon sleeve; The self-lubricating microcapsules are prepared by the following steps: Step A1: Mix commercially available Runxingyuan CP1000 polyvinyl alcohol and deionized water, stir for 1 hour at a stirring rate of 300 rpm and a temperature of 85°C, then add ammonia water to adjust the pH value to 8, add commercially available serrata lignin and ionic liquid, then add hydrochloric acid solution to adjust the pH value to 3, emulsify for 10 minutes at a stirring rate of 8000 rpm to obtain a composite emulsion; The mass concentration of ammonia water is 25%, the molar concentration of hydrochloric acid solution is 1 mol / L, and the dosage ratio of polyvinyl alcohol, deionized water, lignin and ionic liquid is 0.4 g: 120 mL: 0.8 g: 1.2 g; Step A2: isophorone diisocyanate and triethylenetetramine are mixed, stirred at a stirring rate of 450 rpm and a temperature of 50°C, and then added dropwise to the composite emulsion for reaction for 3 hours to obtain single-wall microcapsules; tris(hydroxymethyl)aminomethane hydrochloride) solution and dopamine hydrochloride are mixed, stirred at a stirring rate of 120 rpm and a temperature of 40°C, and then added to the single-wall microcapsules for reaction for 0.5 hours; polyethyleneimine is then added, and the reaction is continued for 3-4 hours to obtain modified microcapsules; The amount ratio of isophorone diisocyanate, triethylenetetramine and composite emulsion is 0.0014mol:0.0012mol:120mL, the mass concentration of tris(hydroxymethyl)aminomethane hydrochloride solution is 1.2g / L, the pH value is 8, the amount ratio of tris(hydroxymethyl)aminomethane hydrochloride solution, dopamine hydrochloride, single-wall microcapsule and polyethyleneimine is 100mL:0.24g:0.04g:0.2g; Step A3: Mix commercially available Hongwu Nano 120nm graphene oxide, ammonium tetrathiomolybdate and anhydrous ethanol, stir and add ascorbic acid at a stirring rate of 300 rpm and a temperature of 110°C, react for 3 hours to obtain a precursor, mix the precursor with deionized water, and ultrasonically disperse for 10 minutes, stir and add modified microcapsules at a stirring rate of 150 rpm and room temperature, react for 6 hours, then add 3-glycidyloxypropyltrimethoxysilane and anhydrous ethanol, react for 2 hours to obtain self-lubricating microcapsules; The amount ratio of graphene oxide, ammonium tetrathiomolybdate, anhydrous ethanol and ascorbic acid is 0.5g:1g:60mL:2g, and the amount ratio of precursor, deionized water, modified microcapsule, 3-glycidyloxypropyltrimethoxysilane and anhydrous ethanol is 0.3g:100mL:1.5g:4.5mL:60mL; The ionic liquid is prepared by the following steps: Step B1: dimethyl chlorophosphate, hydroxyethyl acrylate and dichloromethane are mixed, stirred at a stirring rate of 120 rpm, at room temperature, triethylamine is added, and the reaction is carried out for 6 hours to obtain intermediate a; intermediate a, 3-amino-1-propanol and dimethyl sulfoxide are mixed, and the reaction is carried out for 24 hours under nitrogen protection, at a stirring rate of 120 rpm and a temperature of 60° C. to obtain intermediate b; intermediate b, 4-dimethylaminopyridine, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and dimethyl sulfoxide are mixed, and the reaction is carried out at a stirring rate of 120 rpm, at room temperature, thioctic acid is added, and the reaction is carried out for 24 hours to obtain intermediate c; The amount ratio of dimethyl chlorophosphate, hydroxyethyl acrylate and triethylamine is 0.1mol:0.12mol:12g, the amount ratio of intermediate a and 3-amino-1-propanol is 0.1mol:0.05mol, the amount ratio of intermediate b, 4-dimethylaminopyridine, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and thioctic acid is 0.045mol:11g:18g:0.05mol; Step B2: 1-(3-aminopropyl)imidazole, 1,6-hexamethylene diisocyanate and chloroform were mixed, and the mixture was reacted for 4 h at a stirring rate of 80 rpm and a temperature of 80° C. to obtain intermediate d. Intermediate c, intermediate d and ether were mixed, and dicyclohexylcarbodiimide was added under stirring at a stirring rate of 80 rpm and a temperature of 40° C., and the mixture was reacted for 12 h to obtain an ionic liquid. The ratio of 1-(3-aminopropyl)imidazole to 1,6-diisocyanatohexane is 0.1 mol:0.05 mol, and the ratio of intermediate c, intermediate d and dicyclohexylcarbodiimide is 0.04 mol:0.04 mol:2.5 g.

[0008] Example 2 A method for preparing a wear-resistant nylon sleeve comprises the following steps: Step S1: Weigh the following raw materials in parts by weight: 100 parts of commercially available Shunjie 200 mesh nylon 6, 6 parts of self-lubricating microcapsules, 1.2 parts of carbon black, 3 parts of commercially available OP1240 flame retardant and 1 part of commercially available 1010 antioxidant; Step S2: mixing nylon 6, self-lubricating microcapsules, carbon black, flame retardant and antioxidant, removing water under vacuum and feeding into a mold, centrifuging and reacting for 20 minutes at a temperature of 180° C., demoulding and cooling to obtain a wear-resistant nylon sleeve; The self-lubricating microcapsules are prepared by the following steps: Step A1: Mix commercially available Runxingyuan CP1000 polyvinyl alcohol and deionized water, stir for 1 hour at a stirring rate of 300 rpm and a temperature of 85°C, then add ammonia water to adjust the pH value to 8, add commercially available serrata lignin and ionic liquid, then add hydrochloric acid solution to adjust the pH value to 3, emulsify for 10 minutes at a stirring rate of 8000 rpm to obtain a composite emulsion; The mass concentration of ammonia water is 25%, the molar concentration of hydrochloric acid solution is 1 mol / L, and the dosage ratio of polyvinyl alcohol, deionized water, lignin and ionic liquid is 0.5 g: 120 mL: 1 g: 1.5 g; Step A2: isophorone diisocyanate and triethylenetetramine are mixed, stirred at a stirring rate of 500 rpm and a temperature of 50°C, and then added dropwise to the composite emulsion for reaction for 3 hours to obtain single-wall microcapsules; tris(hydroxymethyl)aminomethane hydrochloride) solution and dopamine hydrochloride are mixed, stirred at a stirring rate of 150 rpm and a temperature of 40°C, and then added to the single-wall microcapsules for reaction for 0.5 hours; polyethyleneimine is then added, and the reaction is continued for 3 hours to obtain modified microcapsules; The amount ratio of isophorone diisocyanate, triethylenetetramine and composite emulsion is 0.0015mol:0.0012mol:150mL, the mass concentration of tris(hydroxymethyl)aminomethane hydrochloride solution is 1.2g / L, the pH value is 8, the amount ratio of tris(hydroxymethyl)aminomethane hydrochloride solution, dopamine hydrochloride, single-wall microcapsule and polyethyleneimine is 120mL:0.24g:0.05g:0.2g; Step A3: Mix commercially available Hongwu Nano 120nm graphene oxide, ammonium tetrathiomolybdate and anhydrous ethanol, stir and add ascorbic acid at a stirring rate of 300rpm and a temperature of 110°C, react for 3-4h to obtain a precursor, mix the precursor with deionized water, and ultrasonically disperse for 10min, stir and add modified microcapsules at a stirring rate of 180rpm and room temperature, react for 6h, then add 3-glycidyloxypropyltrimethoxysilane and anhydrous ethanol, react for 3h to obtain self-lubricating microcapsules; The amount ratio of graphene oxide, ammonium tetrathiomolybdate, anhydrous ethanol and ascorbic acid is 0.8g:1.2g:60mL:2.2g, and the amount ratio of precursor, deionized water, modified microcapsule, 3-glycidyloxypropyltrimethoxysilane and anhydrous ethanol is 0.3g:120mL:2g:4.5mL:80mL; The ionic liquid is prepared by the following steps: Step B1: dimethyl chlorophosphate, hydroxyethyl acrylate and dichloromethane were mixed, stirred at a stirring rate of 150 rpm, at room temperature, triethylamine was added, and the reaction was carried out for 6 hours to obtain intermediate a; intermediate a, 3-amino-1-propanol and dimethyl sulfoxide were mixed, and the reaction was carried out for 24 hours under nitrogen protection, stirring at a rate of 150 rpm, and a temperature of 60° C. to obtain intermediate b; intermediate b, 4-dimethylaminopyridine, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and dimethyl sulfoxide were mixed, stirred at a stirring rate of 120 rpm, at room temperature, thioctic acid was added, and the reaction was carried out for 24 hours to obtain intermediate c; The amount ratio of dimethyl chlorophosphate, hydroxyethyl acrylate and triethylamine is 0.12mol:0.14mol:12g, the amount ratio of intermediate a and 3-amino-1-propanol is 0.1mol:0.05mol, the amount ratio of intermediate b, 4-dimethylaminopyridine, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and thioctic acid is 0.05mol:11g:19g:0.05mol; Step B2: 1-(3-aminopropyl)imidazole, 1,6-hexamethylene diisocyanate and chloroform were mixed, and the mixture was reacted for 4 h at a stirring rate of 100 rpm and a temperature of 80° C. to obtain intermediate d. Intermediate c, intermediate d and ether were mixed, and dicyclohexylcarbodiimide was added under stirring at a stirring rate of 100 rpm and a temperature of 40° C., and the mixture was reacted for 12 h to obtain an ionic liquid. The ratio of 1-(3-aminopropyl)imidazole to 1,6-diisocyanatohexane is 0.11 mol:0.05 mol, and the ratio of intermediate c, intermediate d and dicyclohexylcarbodiimide is 0.04 mol:0.045 mol:2.5 g.

[0009] Example 3 A method for preparing a wear-resistant nylon sleeve comprises the following steps: Step S1: Weigh the following raw materials in parts by weight: 100 parts of commercially available Shunjie 200 mesh nylon 6, 8 parts of self-lubricating microcapsules, 1.2 parts of carbon black, 3 parts of commercially available OP1240 flame retardant and 1 part of commercially available 1010 antioxidant; Step S2: mixing nylon 6, self-lubricating microcapsules, carbon black, flame retardant and antioxidant, removing water under vacuum and feeding into a mold, centrifuging and reacting for 20 minutes at a temperature of 180° C., demoulding and cooling to obtain a wear-resistant nylon sleeve; The self-lubricating microcapsules are prepared by the following steps: Step A1: Mix commercially available Runxingyuan CP1000 polyvinyl alcohol and deionized water, stir for 1 hour at a stirring rate of 300 rpm and a temperature of 85°C, then add ammonia water to adjust the pH value to 8, add commercially available serrata lignin and ionic liquid, then add hydrochloric acid solution to adjust the pH value to 3, emulsify for 10 minutes at a stirring rate of 8000 rpm to obtain a composite emulsion; The mass concentration of ammonia water is 25%, the molar concentration of hydrochloric acid solution is 1 mol / L, and the dosage ratio of polyvinyl alcohol, deionized water, lignin and ionic liquid is 0.5 g: 150 mL: 1 g: 1.5 g; Step A2: isophorone diisocyanate and triethylenetetramine are mixed, stirred at a stirring rate of 500 rpm and a temperature of 50°C, and then added dropwise to the composite emulsion for reaction for 4 hours to obtain single-wall microcapsules; tris(hydroxymethyl)aminomethane hydrochloride) solution and dopamine hydrochloride are mixed, stirred at a stirring rate of 150 rpm and a temperature of 40°C, and then added to the single-wall microcapsules for reaction for 0.5 hours; polyethyleneimine is then added, and the reaction is continued for 3-4 hours to obtain modified microcapsules; The amount ratio of isophorone diisocyanate, triethylenetetramine and composite emulsion is 0.0015mol:0.0013mol:150mL, the mass concentration of tris(hydroxymethyl)aminomethane hydrochloride solution is 1.2g / L, the pH value is 8, the amount ratio of tris(hydroxymethyl)aminomethane hydrochloride solution, dopamine hydrochloride, single-wall microcapsule and polyethyleneimine is 120mL:0.28g:0.05g:0.2g; Step A3: Mix commercially available Hongwu Nano 120nm graphene oxide, ammonium tetrathiomolybdate and anhydrous ethanol, stir and add ascorbic acid at a stirring rate of 300 rpm and a temperature of 110°C, react for 4 hours to obtain a precursor, mix the precursor with deionized water, and ultrasonically disperse for 10 minutes, stir and add modified microcapsules at a stirring rate of 180 rpm and room temperature, react for 8 hours, then add 3-glycidyloxypropyltrimethoxysilane and anhydrous ethanol, react for 3 hours to obtain self-lubricating microcapsules; The amount ratio of graphene oxide, ammonium tetrathiomolybdate, anhydrous ethanol and ascorbic acid is 0.8g:1.2g:80mL:2.2g, and the amount ratio of precursor, deionized water, modified microcapsule, 3-glycidyloxypropyltrimethoxysilane and anhydrous ethanol is 0.4g:120mL:2g:5mL:80mL; The ionic liquid is prepared by the following steps: Step B1: dimethyl chlorophosphate, hydroxyethyl acrylate and dichloromethane were mixed, stirred at a stirring rate of 150 rpm, at room temperature, triethylamine was added, and the reaction was carried out for 8 hours to obtain intermediate a; intermediate a, 3-amino-1-propanol and dimethyl sulfoxide were mixed, and the reaction was carried out for 24 hours under nitrogen protection, stirring at a rate of 150 rpm, and a temperature of 60° C. to obtain intermediate b; intermediate b, 4-dimethylaminopyridine, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and dimethyl sulfoxide were mixed, stirred at a stirring rate of 150 rpm, at room temperature, thioctic acid was added, and the reaction was carried out for 24 hours to obtain intermediate c; The amount ratio of dimethyl chlorophosphate, hydroxyethyl acrylate and triethylamine is 0.12mol:0.14mol:13g, the amount ratio of intermediate a and 3-amino-1-propanol is 0.12mol:0.05mol, the amount ratio of intermediate b, 4-dimethylaminopyridine, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and thioctic acid is 0.05mol:12g:19g:0.053mol; Step B2: 1-(3-aminopropyl)imidazole, 1,6-hexamethylene diisocyanate and chloroform were mixed, and the mixture was reacted for 6 hours at a stirring rate of 100 rpm and a temperature of 80°C to obtain intermediate d. Intermediate c, intermediate d and ether were mixed, and dicyclohexylcarbodiimide was added under stirring at a stirring rate of 100 rpm and a temperature of 40°C, and the mixture was reacted for 14 hours to obtain an ionic liquid. The ratio of 1-(3-aminopropyl)imidazole to 1,6-diisocyanatohexane is 0.11 mol:0.05 mol, and the ratio of intermediate c, intermediate d and dicyclohexylcarbodiimide is 0.045 mol:0.045 mol:3 g.

[0010] Comparative Example 1 Compared with Example 3, this comparative example is different in that the ionic liquid in the process of preparing the self-lubricating microcapsules in Example 3 is replaced by commercially available 1-butyl-3-methylimidazolium tetrafluoroborate ionic liquid, and the other steps are the same.

[0011] Comparative Example 2 Compared with Example 3, this comparative example is different in that the precursor in the process of preparing the self-lubricating microcapsules in Example 3 is replaced with commercially available Hongwu Nano 120 nm graphene oxide, and the other steps are the same.

[0012] Comparative Example 3 Compared with Example 3, this comparative example replaces the self-lubricating microcapsules in the preparation process of the wear-resistant nylon sleeve in Example 3 with the modified microcapsules in Example 3, and the other steps are the same.

[0013] Take the wear-resistant nylon sleeves prepared in Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2 and Comparative Example 3, and test their friction properties with reference to GB / T 3960-2016. Use a GCr15 bearing steel ball with a diameter of 6 mm as a grinding pair, the contact pressure is 80 MPa and 100 MPa, the ball head reciprocating distance is 5 mm, the frequency is 4 Hz, and the single test time is 30 min. The wear rate and friction coefficient are calculated. The test results are shown in Table 1 below: Table 1 Test results Test items Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 <![CDATA[Wear rate at 80 MPa (mm 3 / N * m) * 10 -6 > 2.39 2.20 2.17 3.30 2.89 13.21 <![CDATA[Wear rate at 100 MPa (mm 3 / N * m) * 10 -6 > 3.46 3.32 3.24 4.71 4.07 15.42 Average friction coefficient at 80MPa 0.098 0.091 0.087 0.154 0.129 0.318 It can be seen from the test results in the table shown that Example 1, Example 2 and Example 3 are compared with Comparative Example 1, Comparative Example 2 and Comparative Example 3. In Comparative Example 1, the ionic liquid in the preparation process of the self-lubricating microcapsules in Example 3 is replaced by the commercially available 1-butyl-3-methylimidazolium tetrafluoroborate ionic liquid. Due to the lack of the twin structure and its functional groups, its self-lubricating performance is greatly reduced, which in turn leads to an increase in the wear rate and the friction coefficient. In Comparative Example 2, the precursor in the preparation process of the self-lubricating microcapsules in Example 3 is replaced by commercially available graphene oxide. Due to the lack of nano-molybdenum disulfide accumulation, the ionic liquid cannot be non-covalently bonded to the precursor, and the disordered accumulation of the lamellar precursor causes its wear rate and friction coefficient to increase. In Comparative Example 3, the self-lubricating microcapsules in the preparation process of the wear-resistant nylon sleeve in Example 3 are replaced by the modified microcapsules in Example 3. Due to the lack of the precursor layer, the microcapsules are damaged during the preparation of the nylon sleeve, resulting in leakage of the core material, which in turn affects its wear rate and friction coefficient.

[0014] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0015] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing a wear-resistant nylon sleeve, characterized in that: The method comprises the following steps: Step S1: weighing the following raw materials in parts by weight: 90-100 parts of nylon 6, 6-8 parts of self-lubricating microcapsules, 1-1.2 parts of carbon black, 2-3 parts of flame retardant and 0.8-1 part of antioxidant; Step S2: Nylon 6, self-lubricating microcapsules, carbon black, flame retardant and antioxidant are mixed and vacuum-dried and put into a mold, centrifuged and reacted for 20 minutes at a temperature of 180° C., demolded, and cooled to obtain a wear-resistant nylon sleeve.

2. The method for preparing a wear-resistant nylon sleeve according to claim 1, characterized in that: The self-lubricating microcapsules are prepared by the following steps: Step A1: polyvinyl alcohol and deionized water were mixed, stirred at a stirring rate of 300 rpm and a temperature of 85° C. for 1 hour, and then ammonia water was added to adjust the pH value to 8, and lignin and ionic liquid were added, and then hydrochloric acid solution was added to adjust the pH value to 3, and emulsified at a stirring rate of 8000 rpm for 10 minutes to obtain a composite emulsion; Step A2: isophorone diisocyanate and triethylenetetramine are mixed, stirred at a stirring rate of 450-500 rpm and a temperature of 50°C, and then dripped into the composite emulsion for reaction for 3-4 hours to obtain single-wall microcapsules; tris(hydroxymethyl)aminomethane hydrochloride) solution and dopamine hydrochloride are mixed, stirred at a stirring rate of 120-150 rpm and a temperature of 40°C, and then added into the single-wall microcapsules for reaction for 0.5 hours; polyethyleneimine is then added, and the reaction is continued for 3-4 hours to obtain modified microcapsules; Step A3: Graphene oxide, ammonium tetrathiomolybdate and anhydrous ethanol are mixed, stirred at a stirring rate of 300 rpm and a temperature of 110°C, ascorbic acid is added, and the reaction is carried out for 3-4 hours to obtain a precursor, the precursor is mixed with deionized water, and ultrasonically dispersed for 10 minutes, stirred at a stirring rate of 150-180 rpm and room temperature, and modified microcapsules are added, and the reaction is carried out for 6-8 hours, and 3-glycidyloxypropyltrimethoxysilane and anhydrous ethanol are added, and the reaction is carried out for 2-3 hours to obtain self-lubricating microcapsules.

3. The method for preparing a wear-resistant nylon sleeve according to claim 2, characterized in that: In step A1: the mass concentration of ammonia water is 25%, the molar concentration of hydrochloric acid solution is 1 mol / L, and the dosage ratio of polyvinyl alcohol, deionized water, lignin and ionic liquid is 0.4-0.5 g: 120-150 mL: 0.8-1 g: 1.2-1.5 g.

4. The method for preparing a wear-resistant nylon sleeve according to claim 2, characterized in that: In step A2, the amount ratio of isophorone diisocyanate, triethylenetetramine and composite emulsion is 0.0014-0.0015 mol: 0.0012-0.0013 mol: 120-150 mL, the mass concentration of tris(hydroxymethyl)aminomethane hydrochloride solution is 1.2 g / L, the pH value is 8, and the amount ratio of tris(hydroxymethyl)aminomethane hydrochloride solution, dopamine hydrochloride, single-wall microcapsule and polyethyleneimine is 100-120 mL: 0.24-0.28 g: 0.04-0.05 g: 0.2 g.

5. The method for preparing a wear-resistant nylon sleeve according to claim 2, characterized in that: In step A3: the amount ratio of graphene oxide, ammonium tetrathiomolybdate, anhydrous ethanol and ascorbic acid is 0.5-0.8 g: 1-1.2 g: 60-80 mL: 2-2.2 g, and the amount ratio of precursor, deionized water, modified microcapsule, 3-glycidyloxypropyltrimethoxysilane and anhydrous ethanol is 0.3-0.4 g: 100-120 mL: 1.5-2 g: 4.5-5 mL: 60-80 mL.

6. The method for preparing a wear-resistant nylon sleeve according to claim 2, characterized in that: The ionic liquid is prepared by the following steps: Step B1: dimethyl chlorophosphate, hydroxyethyl acrylate and dichloromethane are mixed, stirred at a stirring rate of 120-150 rpm, at room temperature, triethylamine is added, and the reaction is carried out for 6-8 hours to obtain intermediate a; intermediate a, 3-amino-1-propanol and dimethyl sulfoxide are mixed, and the reaction is carried out for 24 hours under nitrogen protection, at a stirring rate of 120-150 rpm, and at a temperature of 60° C. to obtain intermediate b; intermediate b, 4-dimethylaminopyridine, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and dimethyl sulfoxide are mixed, and the reaction is carried out at a stirring rate of 120-150 rpm, at room temperature, thioctic acid is added, and the reaction is carried out for 24 hours to obtain intermediate c; Step B2: 1-(3-aminopropyl)imidazole, 1,6-hexamethylene diisocyanate and trichloromethane were mixed, and the mixture was reacted for 4-6 hours at a stirring rate of 80-100 rpm and a temperature of 80°C to obtain intermediate d. Intermediate c, intermediate d and ether were mixed, and dicyclohexylcarbodiimide was added at a stirring rate of 80-100 rpm and a temperature of 40°C, and the mixture was stirred for 12-14 hours to obtain an ionic liquid.

7. The method for preparing a wear-resistant nylon sleeve according to claim 6, characterized in that: In step B1: the amount ratio of dimethyl chlorophosphate, hydroxyethyl acrylate and triethylamine is 0.1-0.12mol: 0.12-0.14mol: 12-13g, the amount ratio of intermediate a and 3-amino-1-propanol is 0.1-0.12mol: 0.05mol, and the amount ratio of intermediate b, 4-dimethylaminopyridine, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and thioctic acid is 0.045-0.05mol: 11-12g: 18-19g: 0.05-0.053mol.

8. The method for preparing a wear-resistant nylon sleeve according to claim 6, characterized in that: In step B2: the ratio of 1-(3-aminopropyl)imidazole and 1,6-diisocyanatohexane is 0.1-0.11 mol:0.05 mol, and the ratio of intermediate c, intermediate d and dicyclohexylcarbodiimide is 0.04-0.045 mol:0.04-0.045 mol:2.5-3 g.

9. A wear-resistant nylon sleeve, characterized in that: Prepared according to any one of the preparation methods described in claims 1-8.

Citation Information

Cited By

  • Wear-resistant nylon bar and preparation method thereof

    CN120399443A